Halimah Mohd Said, Kalaivani Nadarajah, Sivachandralingam Sundara Raja and Asma Abdullah, eds. History for Nation Building. Kuala Lumpur: PCORE, 2018. 204 pp. ISBN 978-983-3221-83-7. - Ahmad, Khairil Izamin (IIUMPress, International Islamic University Malaysia, 2018)
Malaysia has arrived at an exciting moment in its history. With the result of its fourteenth general election (GE14), which took place on 9 May 2018, the 61-year rule of Barisan Nasional (BN) has come to an end. BN’s rule, which was marked mostly by its communitarian approach, has hitherto set the tone for how the Malaysian public spaces approach their social discourses, including on the understanding of the country’s history. By extension, nation building has come to mirror the image of the racialised perimeters of BN’s – particularly UMNO’s – politics.